IMPLEMENTASI PROGRAM PENDIDIKAN KARAKTER PADA ELEMEN BERKEBHINEKAAN GLOBAL DI KELAS IV SDN 3 ABIANSEMAL - Astuti, Ni Putu Eni; Dewi, Ni Made Kusuma (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Students' understanding of global diversity at SDN 3 Abiansemal has begun to develop, but is still limited. Students tend to still be in groups with friends with similar backgrounds, and the application of diversity values ​​is conveyed more theoretically than practically. Based on these problems, researchers want to know the application of the character education program to the Pancasila profile of global diversity elements at SD N 3 Abiansemal. This research aims to analyze the implementation of a character education program on elements of global diversity in class IV at SDN 3 Abiansemal. The research method used is qualitative with a descriptive approach, involving observation and interviews. The subjects of this research were teachers and students of class IV SD N 3 Abiansemal. The data analysis process is carried out through the stages of data reduction, data presentation, and drawing conclusions from the information obtained during observation. This research uses primary data sources as the main material. The results show that the character education program in class IV of SDN 3 Abiansemal succeeded in increasing students' understanding of local culture and attitudes of tolerance. Extracurricular activities, such as traditional dance and crafts, as well as the integration of P5 material, strengthen the values ​​of mutual cooperation and mutual respect. Project activities and interactive discussions develop intercultural communication and strengthen the sense of community, preparing students to face social and cultural challenges.